Fairness in Higher Education Research and Innovation Funding in the UK - Champika L. Liyanage; Felix Villalba-Romero; Andrew Carmichael (Trends in Higher Education)
This research analysed the distribution of publicly awarded funding, by United Kingdom Research and Innovation (UKRI) to defined University Groups and compared it against the aim and objectives of UKRI’s Equality, Diversity, and Inclusivity (EDI) strategy. Previous work has identified failures in the allocation of research awards, with some groups being under-represented in successful bids. UKRI have acknowledged that the situation needs to improve yet concern exists over whether change has been enacted. Publicly accessible information provided freely by UKRI was used in conducting a comprehensive analysis of the current position. The results showed that the marginalisation of groups applies at a University Group level, with over-representation of the elite universities of the Russell Group in successfully funded project bids. The data show how, both in total financial expenditure and in the number of projects financed, the awarding of research funding to the universities with the largest popular base, namely the group identified as Post-92 universities, is relatively very small. These universities, as identified by measurements such as social inclusion within university rankings, contribute to greater equality of opportunities for student populations and reduce the impact of economic discrimination. By greatly minoritising the Post-92 universities through funding, UKRI is effectively reducing access for their disadvantaged students.